Separation Enhancement of Mechanical Filters by Adding Negative Air Ions - Yang, Shinhao; Huang, Yi Chin; Luo, Chin Hsiang; Chuang, Chi-Yu (Journal of Membrane and Separation Technology, 2017)
The purpose of this work is to combine negative air ions (NAIs) and mechanical filters for removal of indoor suspended particulates. Various factors, including aerosol size (0.05-0.45 μm), face velocity (10 and 20 cm/s), species of aerosol (potassium chloride and dioctyl phthalate), relative humidity (30% and 70%), and concentrations of NAIs (2 ´ 104, 1 ´ 105, and 2 ´ 105 NAIs/cm3) were considered to evaluate their effects on the aerosol collection characteristics of filters. Results show that the aerosol penetration through the mechanical filter is higher than that through the mechanical filters cooperated with NAIs. This finding implies that the aerosol removal efficiency of mechanical filters can be improved by NAIs. Furthermore, the aerosol penetration through the mechanical filters increased with the aerosol size when NAIs were added. That is due to that the aerosol is easier to be charged when its size gets larger. The results also indicate the aerosol penetration decreased with the NAIs concentration increased. Reversely, aerosol penetration through the mechanical filters increased with the face velocity under the influence of NAIs. The aerosol penetration through the filter with NAIs was no affected with relative humidity. Finally, The penetration through the filter with NAIs against solid aerosol was lower than that against liquid aerosol.